Pengaruh Pengungkapan Corporate Social Responsibility Terhadap Nilai Perusahaan Dengan Financial Distress Sebagai Variabel Moderasi - Katarina Feliska Kurniawan; I Putu Sugiartha Sanjaya (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
Disclosure of corporate social responsibility is regulated in Law Number 40 of 2007 Article 74. Disclosure of CSR provides benefits for both the community and the company. CSR disclosure can improve the company's reputation. A good reputation will increase the value of the company in the eyes of the community. In fact, there are still cases of misuse of CSR funds in Indonesia, such as cases of corruption and money laundering. Companies may do CSR to cover a situation, such as financial difficulties. This will make the value of the company decrease due to the element of imagery and is considered unfavorable by investors. This study aims to provide empirical evidence regarding the effect of corporate social responsibility disclosure on firm value with financial distress as a moderating variable. The research was conducted on manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The dependent variable in this study is the value of the company as proxied by Tobin's Q. The independent variable in this study is corporate social responsibility which is measured using the GRI G4 index. The moderating variable in this study is financial distress as measured by the Altman and Zmijewski models. The control variables used in this study are leverage, growth, and cash ratio. The results show that corporate social responsibility has a positive effect on firm value. The results also show that financial distress does not affect the relationship between corporate social responsibility and firm value.